A pilot study on sensitivity and specificity of cystatin c in detecting renal impairment in hypertensive pregnancies - Jummaat , Fauziah (2011)
Objectives : This study is to compare between Cystatin C and 24 hour urine creatinine clearance for detection of renal impairment in hypertensive pregnancies population. Study Methods: 64 patients enrolled in this cross sectional study and each patient was required to collect 24 hour urine and 15 mls of blood. Blood taking was taken once in second and third trimester. Urine collection was carried out during the first visit. Creatinine clearance below 90 mls/min is taken as renal impairment and compared to the serum Cystatin C level. The Receiver Operating Characteristic Curve is drawn to obtain the sensitivity and specificity of Cystatin C. Results : The results have shown that when compared to 24 hour urine creatinine clearance, in second trimester, Cystatin C is 84.6 % sensitive and 86.7% specific for detection of renal impairment at Cystatin C level of 0.574-0.898 (p value < 0.012) , area under curve: 0.736, positive predictive value is 0.92 and negative predictive value is 0.76. While in the third trimester, the sensitivity and specificity is 76.9% and 60% at the Cystatin C level of 0.657-1.00 (p value < 0.006), area under curve 0.838, the positive predictive value is 0.71 and negative predictive value is 0.67. Conclusion: Our study suggests that Cystatin C is a useful diagnostic kit for diagnosis of renal impairment in hypertensive pregnancies population.